Addressing Afghan Refugee Mental Health through Culturally Fluent Interventions: A Call to Incorporate Lay Mental Health Workers while Addressing SDOH - Ahmadi-Montecalvo, Halima; Terry, Amanda; Rogers, Rosalind (My University, 2024)
While the world’s attention for the plight of refugees and asylum seekers tends to shift with new global conflicts, this paper will highlight the challenges in diagnosing and delivering culturally appropriate mental health care for Afghan refugees in the United States who report more significant psychological distress, adverse living conditions, and post-resettlement mental health problems than other migrant groups. This publication is part of a series highlighting the work and analysis of the Afghanistan Research Network (ARN), a project convened by LSE / PeaceRep, and the Civic Engagement Project (CEP). The network brings together over 20 Afghan researchers (and several non-Afghans) with diverse expertise and backgrounds investigating a range of issues. This project aims to support Afghan researchers who were recently forced to leave Afghanistan; to ensure expert and analytical provision; inform contextually-appropriate international policies and practices on Afghanistan; and to deepen understanding of evolving political, security, and economic dynamics.
Keywords: Peace Processes; Afghanistan